2017
DOI: 10.18352/ulr.413
|View full text |Cite
|
Sign up to set email alerts
|

On Why Procedural Justice Matters in Court Hearings: Experimental Evidence that Behavioral Disinhibition Weakens the Association between Procedural Justice and Evaluations of Judges

Abstract: Recent debates have questioned the robustness of priming effects in experimental social psychology. Here we present results from two randomized controlled field experiments, conducted in courtrooms among actual litigants, that may contribute to the robustness of our field.Specifically, we examine how litigants respond to court hearings pertaining to important decisions about their bankruptcy (Study 1) and criminal sentences that can be imposed on them (Study 2). In studying litigants' reactions to these hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…A body of research that explored the relationship between the experience of the legal process and the attitudes of the court participants towards courts (Casper, 1978;Lind & Tyler, 1988;Tyler, 1990;Benesh & Howell, 2001;Benesh, 2006;Thibaut & Walker, 1975) support the argument that attitudes and opinions regarding courts are associated with a number of socially and legally desirable outcomes. These include higher rate of acceptance of court decisions (Lind, Kulik, Ambrose, & de Vera Park, 1993), increased belief in legitimacy (Hough, Jackson, Bradford, Myhill, & Quinton, 2010;Hulst, Van den Bos, Akkermans, & Lind, 2017;Tyler & Huo, 2002), as well as obedience to laws (Tyler, 2006). In other words, viewing the process as fair has been found to be associated with positive attitudes towards courts in general, with more favorable views of court's decisions, and with higher compliance with those decisions as well.…”
Section: How Going To Court Affects the Attitudes Towards Courtsmentioning
confidence: 99%
“…A body of research that explored the relationship between the experience of the legal process and the attitudes of the court participants towards courts (Casper, 1978;Lind & Tyler, 1988;Tyler, 1990;Benesh & Howell, 2001;Benesh, 2006;Thibaut & Walker, 1975) support the argument that attitudes and opinions regarding courts are associated with a number of socially and legally desirable outcomes. These include higher rate of acceptance of court decisions (Lind, Kulik, Ambrose, & de Vera Park, 1993), increased belief in legitimacy (Hough, Jackson, Bradford, Myhill, & Quinton, 2010;Hulst, Van den Bos, Akkermans, & Lind, 2017;Tyler & Huo, 2002), as well as obedience to laws (Tyler, 2006). In other words, viewing the process as fair has been found to be associated with positive attitudes towards courts in general, with more favorable views of court's decisions, and with higher compliance with those decisions as well.…”
Section: How Going To Court Affects the Attitudes Towards Courtsmentioning
confidence: 99%
“…Impressions of the process and procedures used by authorities are typically available to the perceiver, forming the heart of the fairness heuristic (Lind et al., 1993). Individual judgements of fairness on authorities can shape their willingness to accept authority and their compliance with the authority’s decisions (Hulst et al., 2017). Among the many sources of information available to employees, none is more visual than the method of the appointment of representatives in EMCs.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Importantly, Tyler and Huo (2002) show that people's perceptions of procedural fairness are not only related to the perceived legitimacy of individual police officers and judges encountered in personal interactions, but also generalize to overall views of the legitimacy of the police and courts. In line with this, Hulst et al (2017) found that defendants in criminal cases who experienced higher levels of procedural justice during their court hearings assigned greater levels of legitimate power to judges in their country. Perceptions of procedural fairness have also been found to shape views on the legitimacy of the US police (Tyler & Fagan, 2008), Congress (Tyler, 1994) and Supreme Court (Tyler & Rasinski, 1991).…”
Section: Reacting To Procedural Justicementioning
confidence: 63%
“…Perceived procedural fairness also tends to be associated with people's evaluations of decision-making authorities, for instance in terms of trust (Gau, 2010;Grootelaar & Van den Bos, 2018;Hough, Jackson, Bradford, Myhill, & Quinton, 2010;Hulst, Van den Bos, Akkermans, & Lind, 2017;Tyler, 2001). As noted by Grootelaar and Van den Bos (2018, p. 246), " [t]rust is often used as an umbrella term measuring different concepts".…”
Section: Reacting To Procedural Justicementioning
confidence: 99%
See 1 more Smart Citation